2022
DOI: 10.1089/wound.2021.0066
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Scenes of Extracellular Vesicle Therapy for Skin Injuries and Disorders

Abstract: Significance: Skin wounds and disorders compromise the protective functions of skin and patient quality of life. Although accessible on the surface, they are challenging to address due to paucity of effective therapies. Exogenous extracellular vesicles (EVs) and cell-free derivatives of adult multipotent stromal cells (MSCs) are developing as a treatment modality. Knowledge of origin MSCs, EV processing, and mode of action is necessary for directed use of EVs in preclinical studies and methodical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 186 publications
0
1
0
Order By: Relevance
“…The final study applied MSC EVs as enhancers of bone formation in bone grafting (NCT04998058). With such few ongoing trials, there is a real opportunity for future clinical trials to translate the promising findings observed in EV therapeutics in soft tissue areas such as the skin [ 123 ], tendon [ 124 ], heart [ 125 ] or liver [ 126 ] to the orofacial soft tissues.…”
Section: Application Of Stem Cell-derived Extracellular Vesicles For ...mentioning
confidence: 99%
“…The final study applied MSC EVs as enhancers of bone formation in bone grafting (NCT04998058). With such few ongoing trials, there is a real opportunity for future clinical trials to translate the promising findings observed in EV therapeutics in soft tissue areas such as the skin [ 123 ], tendon [ 124 ], heart [ 125 ] or liver [ 126 ] to the orofacial soft tissues.…”
Section: Application Of Stem Cell-derived Extracellular Vesicles For ...mentioning
confidence: 99%